Development of Globular Mobile Robot with Vision System for Monitoring Inside of Piping - MURAMATSU, Masahiro; SUGA, Yasuo; ISHIKAWA, Masato; MURATA, Yuichirou (Transactions of the Japan Society of Mechanical Engineers Series C, 2005)
Piping is used for various places in our life and industries. Recently, since the needs of robots for inspection and maintenance of piping are increasing, mobile robots have been developed in various research institutions. However, a large number of conventional robots were used for piping with larger diameter more than 200 mm, and robots for piping with smaller diameter less than 100 mm are not seen. Furthermore, these robots could not move through any elbow joint and T-joint with right angle or small radius curvature. Accordingly, development of a mobile robot in piping with smaller diameter and various joints, which can apply directly to any pipes laid under ground, in wall, in narrow space and so on, is tried. In particular, in this study, a globular mobile robot with new moving mechanisms and moving algorithms that can move through piping with diammeter about 100 mm is developed. Besides, the robot has vision system, and it can monitor the inside of the piping and detect shape of joint and direction of bend automatically. Finally, the effectiveness of the mobile robot system is verified by moving experiments in piping.